Perceived consumer effectiveness as a trigger of behavioral spillover effects : a path towards recycling (2020)
Increasing and promoting recycling is crucial to achieving sustainable consumption. However, this is a complex task that involves the interplay of beliefs, knowledge and situational factors in ways not yet understood. This study examines a spill-over model in which perceived consumer effectiveness influences the adoption of an easy task (carrying reusable shopping bags) and that, in turn, influences recycling. Using data from a national survey with a representative sample of 1286 respondents in Colombia, we test a hypothesized path using a mediation model. Our results suggest that the relationship between perceived consumer effectiveness and recycling is mediated by the use of reusable shopping bags. Thus, once the adoption of simple pro-environmental behavior is triggered by pro-environmental beliefs, spillover effects may ensue to favor the adoption of recycling behavior. This suggests that individuals may adopt pro-environmental behavior in stages or levels. Therefore, focusing on behaviors that require less effort (e.g., reducing/reusing) could be a starting point when it comes to encouraging the adoption of other behaviors that demand a greater level of effort such as recycling. This study suggests that attitudinal variables can be the starting point of spill-over effects.